Avascular necrosis of bone in systemic lupus erythematosus: possible role of haemostatic abnormalities. Issue 8 (August 1989) - Nagasawa, K; Ishii, Y; Mayumi, T; Tada, Y; Ueda, A; Yamauchi, Y; Kusaba, T; Niho, Y
Abstract : The pathogenesis of avascular necrosis of bone (ANB) was investigated in 111 patients with systemic lupus erythematosus (SLE) (24 with ANB, 87 without ANB); patients' ages, corticosteroid treatment, clinical and laboratory features associated with SLE, and haemostatic profiles were all taken into account. The mean ages of patients with and without ANB at the time of diagnosis of SLE was 24.1 and 31.2 years respectively. The mean maximal daily dose of prednisolone in the group with ANB was 50.8 mg, which was significantly higher than the dose (41.8 mg) in the group without ANB. Disease features of SLE, such as Raynaud's phenomenon, hyperlipidaemia, nephrotic syndrome, hypertension, and disease activity, were not found to be related to ANB. The percentage of patients who had lupus anticoagulant as well as a shorter activated partial thromboplastin time was greater in those with ANB than in those without. Multiple factors may be involved in the pathogenesis of ANB in SLE, and it is suggested that haemostatic abnormalities, which could be influenced by corticosteroids and young ages, play some part in the development of ANB.